PERUBAHAN PENGGUNAAN LAHAN DI DAERAH TANGKAPAN AIR DANAU LIDO DAN PENGURANGAN LUAS PERMUKAAN BADAN AIR DANAU LIDO: Land Use Change in the Lake Lido Catchment Area and Shrinkage in the Water Surface Area of the Lake Lido (Jurnal ForestrIndo, 2025)
The shrinking area of Lake Lido is a critical issue for the management of the Lake Lido Water Catchment Area. Identifying the causing factors is crucial concerning the Lido Lake Water Catchment Area. The objectives of this study are to analyze land-use changes in the Lake Lido Water Catchment Area, changes in the water surface area of Lake Lido, and the causes of the land-use changes and the lake's shrinkage. The available satellite imagery and maps were analyzed using ArcGIS, GEE-Climate Engine, and Excel software. The results indicate that the land use changes in the Lake Lido Water Catchment Area vary, with 21 different types of changes spatially occurring between 2017 and 2024. The total area of built-up land increased, as well as tree-vegetated land, but the agricultural land decreased. The surface area of Lido Lake's water body decreased from 14.5 ha in 2003 to 11.9 ha in 2024. The lake's surface area shrank the most between 2017 and 2024. The reduction of Lake Lido’s water surface area is primarily due to sedimentation in the lake.